2020
DOI: 10.1186/s40709-020-00114-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crocin on antioxidant gene expression, fibrinolytic parameters, redox status and blood biochemistry in nicotinamide-streptozotocin-induced diabetic rats

Abstract: Background: Diabetes is regarded as an epidemiological threat for the twenty-first century. Phytochemicals with known pharmaceutical properties have gained interest in the field of alleviating secondary complications of diseases. Such a substance is crocin, a basic constituent of saffron (Crocus sativus). The present study aimed at examining the beneficial effects of per os crocin administration on the antioxidant status, blood biochemical profile, hepatic gene expression and plasminogen activator inhibitor-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Considering the increasing incidence rate of redox-state related diseases, there is an urgent need to enhance the organisms defense system with minimal side effects. Therefore, naturally occurring compounds with potent antioxidant properties have been extensively used for alleviating the detrimental impacts of such diseases [ 59 , 60 ]. Previous in vitro studies indicated that hyperglycemia is the direct cause of the glycation of cellular matrix proteins of mesonephric kidney cells and renal mesangial cell death [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the increasing incidence rate of redox-state related diseases, there is an urgent need to enhance the organisms defense system with minimal side effects. Therefore, naturally occurring compounds with potent antioxidant properties have been extensively used for alleviating the detrimental impacts of such diseases [ 59 , 60 ]. Previous in vitro studies indicated that hyperglycemia is the direct cause of the glycation of cellular matrix proteins of mesonephric kidney cells and renal mesangial cell death [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…30,61,62 Various articles referred to the antioxidant effects of saffron as the main mechanism for its beneficial effects on diabetic animals. 40,45,49,51,53,54,56,58 Oxidative stress (OS) in uncontrolled hyperglycemia is known to have a fundamental role in pancreatic dysfunction and liver injury. The leading components of the intrinsic anti-oxidation system in the tissues are superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Fifty-four adult male wistar rats with body weight of 200-250 gr were divided into nine experimental groups (n= 6 in each): control group, crocin group: received crocin, 50 mg/kg (19); crocin was suspended in 0.1 ml of normal saline and administered to the rats via intraperitoneal injection); diabetic group: received a single dose of alloxan at 120 mg/kg, IP (22) to induce diabetes; TSP group: 5 mg/kg TSP instilled intratracheally; diabetic-crocin group: received crocin at 50 mg/kg as a single intraperitoneal injection after the induction of diabetes by alloxan (120 mg/kg); diabeticinsulin: received regular insulin (5 U/kg ) as a single subcutaneous injection after the induction of diabetes by alloxan (120 mg/kg) (23); crocin-TSP group: received crocin at 50 mg/kg, IP, and then 5 mg/kg TSP was instilled intratracheally; diabetic-TSP-insulin group: after receiving alloxan (a single dose of 120 mg/kg, IP) and instilling TSP (5 mg/kg, intratracheally), the animals were given a single dose (5 U/kg) of regular insulin by subcutaneous injection; diabetic-TSP-crocin group: after receiving alloxan (a single dose of 120 mg/kg, IP) and instilling TSP (5 mg/kg, intratracheally), the animals were given a single dose of crocin (50 mg/kg, IP).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Antioxidants such as crocin, a natural carotenoid found in Crocus sativus L. (saffron), and Gardenia jasminoides J. Ellis flowers reduce the inflammation and oxidative stress prompted by diabetes and obesity (16,17). The comprehensive antioxidant and anti-inflammatory effects of insulin as a metabolic hormone have been shown with potent effects on glucose and lipid metabolism (18,19). Because of its anti-inflammatory action, insulin can be used as an anti-inflammatory drug (20).…”
Section: Introductionmentioning
confidence: 99%